A class defined "by consumption": The grocery-shopping practices of the Lower-Middle Classes in Johannesburg, South Africa - (:unkn) unknown (My University, 2013)
The black middle class in Johannesburg is a much debated but ill-defined phenomenon, treated more often by economic players than by social scientists. Far from static and clear, the concept of the middle class is for us relevant insofar as it reveals crucial dynamics of the society. Looking more closely at the daily tactics and strategies of the lower-middle class aspiring to a better life, we discovered practices of consumption and saving in groups establishing webs of social networks within the community. In this way, social groups are being constituted. People's own discussion of their habits makes it possible to identify collective representations. While doing that, we try to remain aware of stereotyped inventions on the subject of black people and consumption that pervade not only public discourse but also the views of our interviewees
Keywords: African Research